2018
DOI: 10.2147/cia.s180614
|View full text |Cite
|
Sign up to set email alerts
|

High bone turnover status as a risk factor in symptomatic hypocalcemia following denosumab treatment in a male patient with osteoporosis

Abstract: Denosumab is a fully human monoclonal antibody against the receptor activator of nuclear factor-κB ligand (RANKL) that is used for the treatment of osteoporosis. Denosumab-induced hypocalcemia is a rare but important adverse event, which is usually asymptomatic in patients with osteoporosis. It is also known that hypocalcemia is common in patients with bone metastases and severe renal impairment. Here we report a case of symptomatic hypocalcemia following administration of 60 mg of denosumab in a patient with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 23 publications
0
14
1
Order By: Relevance
“…While previous studies have reported that a higher BR and a lower CSMI are significantly associated with hip fractures,10 our patient fortunately did not develop a fracture. The discrepancy between a previous report that describes no decrease in the BMD at the FN assessed by DXA5 and our case could be due to the relatively long gap of 14 months in the administration of the fifth dose of denosumab with no vertebral fracture in our case. During the delayed interval in denosumab therapy, our patient presented with a transient acute increase in the TRAP-5b and total-P1NP levels.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…While previous studies have reported that a higher BR and a lower CSMI are significantly associated with hip fractures,10 our patient fortunately did not develop a fracture. The discrepancy between a previous report that describes no decrease in the BMD at the FN assessed by DXA5 and our case could be due to the relatively long gap of 14 months in the administration of the fifth dose of denosumab with no vertebral fracture in our case. During the delayed interval in denosumab therapy, our patient presented with a transient acute increase in the TRAP-5b and total-P1NP levels.…”
Section: Discussioncontrasting
confidence: 99%
“…Due to the high persistence with denosumab, promising results for osteoporosis treatment, and convenience of a 6-monthly injection regimen,4 denosumab is widely used. Despite its well-established efficacy for treating osteoporosis, several serious adverse effects of denosumab have been reported,5 including those due to treatment discontinuation. Discontinuation of denosumab leads to the rebound phenomenon, which involves an increase in bone turnover marker levels and decline in BMD 6,7.…”
Section: Introductionmentioning
confidence: 99%
“…As the world's population is aging, the prevalence of chronic diseases has increased. Hence, research on various countermeasures against musculoskeletal diseases, which impair daily living and the quality of life, is urgently needed [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, the serum calcium levels did not change significantly in either group, and this is consistent with the findings of previous studies ( Nakamura et al, 2017 ; Kobayashi et al, 2020 ). However, we previously reported that a high bone turnover elevates the risk of denosumab-induced hypocalcemia ( Ishikawa et al, 2018a ; Ishikawa et al, 2016 ). Therefore, physicians should pay attention to hypocalcemia due to a strong suppression of BTMs in the naïve group.…”
Section: Discussionmentioning
confidence: 99%
“…Osteoporosis was diagnosed in accordance with the criteria established by the Japanese Society of Bone and Mineral Research ( Soen et al, 2013 ). In our institution, we use eldecalcitol (activated vitamin D) 0.75 μg as a prophylactic drug for denosumab to avoid denosumab-induced hypocalcemia ( Ishikawa et al, 2018a ; Ishikawa et al, 2016 ). Patients were divided into the prior bisphosphonate group (prior-BP group) and naïve group based on whether they were previously treated with bisphosphonates.…”
Section: Methodsmentioning
confidence: 99%